(untitled) (Altre Modernità, 2025)
This article aims to integrate the notion of repertoire (understood as complementary and not synonymous with the notion of archive) with the notion of memory which is at the basis of Patrick Modiano’s narrative work. After elaborating a definition of the term ‘repertoire,’ an analysis of four novels by the author is proposed in which, as indeed in all his production, a weak and frayed memory feeds, in its continuous struggle against oblivion, on images resurfaced from the past.